2016
DOI: 10.5530/ijper.50.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa (Kalonji) and Honey on Lipid Profile of Hyper lipidemic Smokers

Abstract: Background:Hyper lipidemia refers to the excess of lipids in the blood of patients. The present study was carried out to investigate the effect of Nigella sativa (kalonji) and honey as compared with Atorvastatin on the lipid profile of hyper lipidemia patients with habit of smoking. Methodology: Purposes, 60 patients (3 groups of 20) of 35-65 years were selected. These patients were treated with 1 g of Nigella sativa (kalonji) seed, one tablespoon of honey, and Atorvastatin 10 mg daily in the morning at fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The consumption of Nigella sativa L seed was a gram per day for 30 days. This treatment had decreased TC, TG, LDL, and increasing HDL [16]. It is still in accordance with those findings, Pourghassem-Gargari et al reported that the Nigella sativa L. powder treatment at dose 7.5 g/kgbw/day and the crushed Nigella sativa L. seed added with 0.5% cholesterol rabbit diet treatment given for two months each have significantly decreased LDL and increased HDL [17].…”
Section: Resultssupporting
confidence: 77%
“…The consumption of Nigella sativa L seed was a gram per day for 30 days. This treatment had decreased TC, TG, LDL, and increasing HDL [16]. It is still in accordance with those findings, Pourghassem-Gargari et al reported that the Nigella sativa L. powder treatment at dose 7.5 g/kgbw/day and the crushed Nigella sativa L. seed added with 0.5% cholesterol rabbit diet treatment given for two months each have significantly decreased LDL and increased HDL [17].…”
Section: Resultssupporting
confidence: 77%
“…Honey mixed with N. sativa has already shown remarkable potential for treating several other diseases. This gives researchers a ray of hope to use this combination in the current pandemic (Ameen et al, 2011;Bhatti et al, 2016;Moghimipour et al, 2019) Bacillus subtilis, isolated from honey, produces a very promising antiviral component known as levan (β-2,6-fructan) that functions against many pathogenic respiratory RNA viruses. By facilitating the aggregation of cells and viruses, levan amplifies the phagocytosis procedure.…”
Section: Nigella Sativa and Honeymentioning
confidence: 99%
“…Also, From table (2) can note that all treated groups decreased significantly as compared to the positive control group. Bhatti et al, (2016) showed that Nigella sativa and honey lowered significantly the levels of total cholesterol (TC), after 30 days of in hyperlipidemic smokers. Buriro and Tayyab (2007) indicated that Nigella sativa seeds in the diet has a favorable The Effects of Nigella Sativa seed and Nigella Sativa Honeybee on Hypercholesterolemic Rats ( 11 ) Egyptian Journal for Specialized Studies -N (16) Oct 2017 effect on lipid profile by lowering the total cholesterol in albino rats.…”
Section: Resultsmentioning
confidence: 99%